2016
DOI: 10.1016/j.xphs.2016.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical Applications of Electrospraying

Abstract: The electrohydrodynamic atomization technique, or simply called electrospraying, has been extensively studied for biomedical as well as for pharmaceutical applications over the past years. The simplicity, flexibility, and efficiency of producing particles at the microscale or nanoscale, with tailored size, shape, morphology, and microstructure, make electrospraying to become one of the most promising and well-practiced approaches to be applied in many biomedical and pharmaceutical fields, from improving the bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
137
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 154 publications
(138 citation statements)
references
References 166 publications
0
137
0
1
Order By: Relevance
“…A high voltage potential on the needle forces the polymer solution out of the syringe and results in the formation of a jet that breaks into monodisperse droplets, which form the microparticles. Electrospraying is associated with many advantages including the ability to fabricate particles with narrow size distribution, its experimental setup requires low investment and it allows for scalable fabrication . A main reason for using electrospraying instead of the common emulsion solvent extraction/evaporation technique is that electrospraying is associated with high entrapment efficiency .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high voltage potential on the needle forces the polymer solution out of the syringe and results in the formation of a jet that breaks into monodisperse droplets, which form the microparticles. Electrospraying is associated with many advantages including the ability to fabricate particles with narrow size distribution, its experimental setup requires low investment and it allows for scalable fabrication . A main reason for using electrospraying instead of the common emulsion solvent extraction/evaporation technique is that electrospraying is associated with high entrapment efficiency .…”
Section: Introductionmentioning
confidence: 99%
“…Electrospraying is associated with many advantages including the ability to fabricate particles with narrow size distribution, its experimental setup requires low investment and it allows for scalable fabrication. 31,32 A main reason for using electrospraying instead of the common emulsion solvent extraction/evaporation technique is that electrospraying is associated with high entrapment efficiency. 32 The effects of solvent used for fabrication (i.e., different volume ratio of dichloromethane [DCM] and acetonitrile) of TMZloaded PLGA microparticles fabricated by electrospraying on drug loading, loading efficiency, drug release kinetics, surface morphology, and particle size were determined.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the working distance, or the distance between the tip and the collector (TTC), is also an important parameter. At a constant voltage, a short distance is advantageous for generating a high electrical field strength, and a long TTC distance would require a higher applied voltage to compensate for the reduced electrical field strength to obtain particles …”
Section: Discussionmentioning
confidence: 99%
“…Another study indicated that electrospray can produce microspheres with a controlled size and morphology at room temperature . Controlling electrospinning parameters in electrospray is a flexible and versatile method to prepare microspheres with customized microstructures and tailored properties, including size, morphology, and shape, for many kinds of biomedical applications . However, some studies have recently shown that there are several limitations associated with microsphere electrospinning, including a difficulty in achieving zero‐order drug release, a lack of long‐term release of drugs, and an initial burst release caused by rapid release of drug located on or near the external surface…”
Section: Introductionmentioning
confidence: 99%
“…Despite all the advantages associated polymers, such as poly-lactide-co-glycolide (PLGA), polycaprolactone (PCL) etc. has found its biggest applications in biomedical engineering [4][5][6][7] and drug delivery [8][9][10][11][12][13][14]. Despite all the advantages associated with electrospraying, nevertheless, the optimization of the spraying procedure has been based on a time-consuming trial-and-error process.…”
Section: Introductionmentioning
confidence: 99%